The existence of financial ratios related anomalies and testing the capital asset pricing model in emerging markets - Kamalanathan, Mayuran (My University, 2012)
This study analyzes the existence of anomalies in the Indian share market. The idea is to construct the portfolios by picking up stocks based on the financial ratios of the India companies. The efficient market theory is also tested because the ratios calculated based on the previous year’s financial performance and creating the portfolio by using that information should not provide greater return than the market at a particular time period. Another aspect of this thesis is test the accuracy of capital asset pricing model in the emerging markets. The findings not give support to the existence of anomalies in India during the observation period. This thesis not finds evidence on the profitability of financial ratios based stocks selecting among the Indian mid capitalized companies during the period. Compared to overall market performance portfolios are managed to create risk adjusted return from time to time. The performance of portfolio including companies with high price to sales ratio has performed well. Another two which come up are low EV/EBITDA and high free cash flow deciles. Adding to this the accuracy of Capital Asset Pricing model has been acceptable during the observation period.
Keywords: Anomaly; India; Capital Asset Pricing model; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|